Patterns of coral species richness and reef connectivity in Malaysia - Zarinah Waheed (Leiden University, 2016)
Much remains to be discovered about the biodiversity of coral reefs in Malaysia, making this area a priority for coral reef research. This thesis aims to provide insights into the patterns of reef coral species richness and the degree of reef connectivity across Malaysia. For the species richness study, the scleractinian coral families Fungiidae, Agariciidae and Euphylliidae were selected as model taxa. Species of these families have a wide geographical distribution in the Indo-Pacific, and they can be found in a large range of reef habitats, from shallow coastal reefs to deep offshore environments. The connectivity of reefs were inferred by examining the genetic population structures of three reef invertebrate species, the mushroom coral Heliofungia actiniformis, the blue seastar Linckia laevigata, and the boring giant clam Tridacna crocea. Data on coral species and specimens of reef invertebrates were collected from reef areas along a geographical range from east to west Malaysia. Reef coral species richness patterns were revealed and indicated common and rare species, as well as potential endemics. Factors to explain the population structure and connectivity patterns across Malaysia are discussed. The findings in this thesis may be relevant for conservation and management of coral reef areas in Malaysia.